Effectiveness Of Loading Unloading Operational Services At New Makassar Container Terminal - Susanti, Eva; Hamsah, Hamsah; Nurwahidah, Nurwahidah; Putra, Rahul Sukhanna; Alvionita, Elysa; Asri, Haerani (Zona Laut Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
This research aims to determine the effectiveness of loading and unloading operational services at the New Makassar Container Terminal. The method that will be used in the research is qualitative by collecting primary and secondary data, then referring to several relevant literature studies, articles and research journals. Based on the analysis above, the efficiency and effectiveness of container loading and unloading activities at the new terminal is effective because the port is divided into two terminals, 60% of ship visits are at Soekarno Hatta (terminal 1) 40% of ship visits are at Makassar new port (Terminal 2), port selection is based on stakeholders, choose the next port, accessibility, distance, and road conditions/congestion at certain access points. The manager loses if the accumulation takes a long time, this is the maximum holding time for coins is 5 days, while the storage accumulation costs are 1 to 5 days with a cost of 18 thousand, if it exceeds the maximum day then there is a fine for storage accumulation with a calculation of 18 thousand per day with a maximum of 10 days. and if it exceeds 10 days, the fine will be increased to 32 thousand per day. The effectiveness of the workforce and infrastructure at the Makassar New Port terminal is very adequate.